The experience of burden in India: A study of dementia caregivers - Leena Mary Emmatty, Ranbir S. Bhatti and Mathew T. Mukalel (Dementia 2006; 5; 223, 2006)
Thirty caregivers of people living with dementia were investigated to examine the caregivers' experience of burden.The Clinical Dementia Rating Scale (CDRS), Burden Interviews and open-ended questions were administered on patients attending inpatient and outpatient services at the National Institute of Mental Health and Neurosciences (NIMHANS), Bangalore (India). Findings indicate that only 30 percent of the cases fell into the high burden group. No statistically significant results were observed between caregiver relationship and burden scores. Burden experienced in extended families was less compared to the other types of families.To conclude, the need to create awareness about the illness among different sections of the general population and interventions suited to the Indian caregivers are discussed.